Finite Dimensional Approximation of Branches of Solutions of Nonlinear Problems near a Cusp Point (Journal of Computational Mathematics, 1989)
This paper presents some results on finite dimensional approximation of branches of solutions of nonlinear problems near a cusp point. These result can be applied to numerical methods of solving nonlinear differential equations.